Unveiling cognitive aspects and accuracy of diagnostic judgments in physical education teachers assessing different tasks in gymnastics - Leukel, Christian; Leuders, Timo; Bessi, Flavio; Loibl, Katharina (Frontiers in Education, 2023)
Diagnostics is an essential part of teachers’ profession. We investigated judgment accuracy and cognitive processes underlying judgment formation in physical education teachers who observed tasks in gymnastics, and compared teachers with gymnastics trainers as a reference group. Teachers and trainers judged performance of prepuberal students in gymnastics, namely students exercising squat vault, underswing, and handstand. To investigate cognitive processes of judgment formation, participants were asked to structure the movements via event segmentation as well as to explain their judgments. All teachers and trainers had experience in working with prepuberal children similar to those they observed in this experiment, and the teachers completed a gymnastics class containing of the three tasks during their studies. Judgment accuracy (with reference to judgments made by expert trainers) was found to be significantly lower in teachers compared to trainers (p < 0.001). Moreover, agreement on the ratings among teachers was lower than among trainers. Agreement about the temporal structuring of the tasks from event segmentation was lower among teachers than among trainers (p < 0.05). When explaining their ratings, trainers referenced to kinematic features that were relevant for structuring the tasks more often than teachers. We discuss these findings in context of the teachers’ task to perform accurate judgments. For suggestions on teacher training, we particularly emphasize the relevance of implementing (declarative) knowledge about kinematic features of the tasks and student errors into real-life scenarios resembling the complex skill of making accurate judgments in the physical education classroom.